Confession and Community in Seventeenth-Century France : Catholic and Protestant Coexistence in Aquitaine - Hanlon, Gregory (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
Examines the tolerance between Catholics and Protestants in a period when vicious sectarian strife was the rule of the day. Tolerance here means more than mere coexistence but a daily interaction between people without regard for their faith.
Frontmatter -- Content -- Acknowledgments -- Introduction -- Part I. "Vivre en union et concorde, unanimement, pour le bien de la République" -- Chapter 1. Was Layrac Typical? -- Chapter 2. The Institutional Community -- Chapter 3. Conflict and Arbitration -- Chapter 4. Sociability and Community -- Part 2." ... N'ayant pu ramener son fils a la Religion" -- Chapter 5. Calvinism from Established Church to Sect -- Chapter 6. Folk Devotion and the Counter-Reformation -- Chapter 7. The Nature of Confessional Ambiguity -- Chapter 8. Religious Identity and Competing Reference Groups -- Chapter 9. European Dimensions of Confessional Coexistence -- Sources -- Bibliography -- Index -- Backmatter
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Dec. 09, 2016).
JSTOR
Keywords: Catholic Church -- France -- Aquitaine -- History -- 17th century; Catholic Church -- History -- 17th century; Église catholique -- Histoire -- 17e siècle.; Catholic Church; Reformed Church -- France -- Aquitaine -- History -- 17th century; Aquitaine (France) -- Church history; Église réformée -- France -- Aquitaine -- Histoire -- 17e siècle.; RELIGION -- Christianity -- History; Reformed Church; France -- Aquitaine; 1600-1699; Church history; History